2010
DOI: 10.1002/pssb.200983970
|View full text |Cite
|
Sign up to set email alerts
|

Coefficient of thermal expansion of stacked auxetic and negative thermal expansion laminates

Abstract: Analytical expressions for the in-plane and out-of-plane coefficients of thermal expansion for laminates with isotropic laminas are presented herein based on (i) zero net force on the laminate edges, (ii) equal displacement of the lamina edges, and (iii) Hooke's law in three dimensions. Results show that a laminate consisting of alternating auxetic (with positive coefficient of thermal expansion, CTE) and negative thermal expansion (NTE) (with positive Poisson's ratio) laminas exhibit a more negative effective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 86 publications
1
19
0
Order By: Relevance
“…It has also been demonstrated that auxetic materials offer a widespread range of applications in the biomedical industry . Moreover, materials that simultaneously have a negative Poisson's ratio and other negative indexes, such as negative compressibility and thermal expansion, could have more emergent physical properties. Such materials with unconventional negative indices have many practical applications, especially in the electronics, medical, aerospace, and defense industries.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been demonstrated that auxetic materials offer a widespread range of applications in the biomedical industry . Moreover, materials that simultaneously have a negative Poisson's ratio and other negative indexes, such as negative compressibility and thermal expansion, could have more emergent physical properties. Such materials with unconventional negative indices have many practical applications, especially in the electronics, medical, aerospace, and defense industries.…”
Section: Introductionmentioning
confidence: 99%
“…Depending on whether negative values of Poisson ratio are observed in all crystallographic directions, in some of them or in none of them, one can define all materials as auxetics, partial auxetics and nonauxetics, respectively (). Recently, increasing interest in studies of auxetic materials and models was observed .…”
Section: Introductionmentioning
confidence: 99%
“…35 ) However, neither predicted the experimental CTE accurately, since they fail to consider material anisotropy. Using Lim's model for stacked laminates, 36 the predicted CTE is À25 9 10 À6 K À1 in the transverse direction (vs À3.5 9 10 À6 K À1 in the longitudinal direction), much more negative than the observed value. However, the observed microstructure is not purely lamellar due to the presence of many bridges between the lamellae.…”
Section: Materials With Controlled Thermal Expansionmentioning
confidence: 85%